Microsoft Project fundamentals : Microsoft Project Standard 2021, Professional 2021, and Project Online editions - Stover, Teresa S. (Sybex, 2022)
Get a firm grip on one of the most popular project management applications on the market today In Microsoft Project Fundamentals: Microsoft Project Standard 2021, Professional 2021, and Project Online Editions, accomplished project management leader Teresa Stover delivers a hands-on introduction to Microsoft's popular project management software filled with real-world examples and plain-language guidance. The book walks you through how to plan, schedule, manage resources, track progress, and more. In the book, you'll: Learn principles and best practices of project management while mastering Microsoft Project capabilities, calculations, and views Understand how task durations, dependencies, and date constraints power the project schedule Manage human, equipment, and material resources, including availability, cost, and task assignments Adjust the project to optimize for the project finish date, budget, and resource allocation Use Microsoft Project to manage waterfall or agile projects Ideal for anyone seeking to unlock the potential of Microsoft's leading project management software for their own project work, Microsoft Project Fundamentals is an essential resource for those new to Microsoft Project and project management, as well as previous users and seasoned project professionals looking for a refresher in the latest features of the newest version of Microsoft Project.